Revisiting the Role of Potassium Sensitivity Testing and Cystoscopic Hydrodistention for the Diagnosis of Interstitial Cystitis - Jiang, Yuan-Hong (PLoS One, 2016)
OBJECTIVES: To revisit the diagnostic roles of cystoscopic hydrodistention and the potassium sensitivity test (PST) for the diagnosis of interstitial cystitis (IC). METHODS: We prospectively enrolled 214 patients clinically diagnosed with IC, 125 non-IC patients who underwent video urodynamic studies and PST, and another 144 non-IC patients who underwent cystoscopic hydrodistention before transurethral surgery. The sensitivity, specificity, and positive and negative predictive values were calculated for the PST and glomerulations after cystoscopic hydrodistention. RESULTS: After cystoscopic hydrodistention, glomerulations developed in 211/214 (98.6%) IC patients and 61/144 (42.4%) of the non-IC patients including patients with stones (45/67, 67%), hematuria (2/5, 40%), and stress urinary incontinence (SUI) (6/17, 35%). When positive glomerulation was defined as grade 2 or more, the sensitivity was 61.7%. The PST was positive in 183/214 (85.5%) IC patients and 7/17 (41%) with hypersensitive bladder, 7/32 (22%) with detrusor overactivity, 5/27 (18%) with SUI, 2/21 (10%) with lower urinary tract symptoms, and 2/25 (8%) with bladder outlet obstruction. The PST had a sensitivity of 85.5% and a specificity of 81.6% for diagnosis of IC. IC patients with a positive PST had a significantly smaller urgency sensation capacity, smaller voided volume, and greater bladder pain score. CONCLUSIONS: Both the PST and glomerulations after hydrodistention are sensitive indicators of IC, but the specificity of glomerulations in the diagnosis of IC is lower than that of the PST. A positive PST is associated with a more hypersensitive bladder and bladder pain, but not the grade of glomerulations in IC patients. Neither test provided 100% diagnostic accuracy for IC, we might select patients into different subgroups based on different PST and hydrodistention results, not for making a diagnosis of IC but for guidance of different treatments.